Responsible Science: Ensuring the Integrity of the Research Process: Volume I - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 1992)
Responsible Science is a comprehensive review of factors that influence the integrity of the research process. Volume I examines reports on the incidence of misconduct in science and reviews institutional and governmental efforts to handle cases of misconduct. The result of a two-year study by a panel of experts convened by the National Academy of Sciences, this book critically analyzes the impact of today's research environment on the traditional checks and balances that foster integrity in science. Responsible Science is a provocative examination of the role of educational efforts; research guidelines; and the contributions of individual scientists, mentors, and institutional officials in encouraging responsible research practices.